2022
DOI: 10.7759/cureus.23217
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Patients With Leprosy Attending a Tertiary Care Institute in North India

Abstract: Introduction Leprosy is a chronic, infectious disease resulting in significant physical and social morbidity. This study aims to assess the nutritional status of patients with leprosy. Methods Treatment-naïve leprosy cases seen over two years at a tertiary care center were recruited in this prospective observational study. Demographic details, type of leprosy, and presence of reactions and disabilities were recorded. Nutritional assessment was done by calculating the body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…16 Jindal et al in 2021 observed 49.5% cases in Borderline Tuberculoid (BT) followed by 21.3% in Lepromatous Leprosy (LL), 14.5% in Borderline Lepromatous (BL), 5.3% in Mid Borderline (BB) and 1.9% cases of Tuberculoid Leprosy (TT). 19 In our study, paucibacillary cases comprised of 30 (66.7%), followed by multibacillary cases; 15 (33.3%). Quaresma et al in 2012 reported equal percentage of paucibacillary and multibacillary cases.…”
Section: Discussionmentioning
confidence: 46%
“…16 Jindal et al in 2021 observed 49.5% cases in Borderline Tuberculoid (BT) followed by 21.3% in Lepromatous Leprosy (LL), 14.5% in Borderline Lepromatous (BL), 5.3% in Mid Borderline (BB) and 1.9% cases of Tuberculoid Leprosy (TT). 19 In our study, paucibacillary cases comprised of 30 (66.7%), followed by multibacillary cases; 15 (33.3%). Quaresma et al in 2012 reported equal percentage of paucibacillary and multibacillary cases.…”
Section: Discussionmentioning
confidence: 46%
“…These studies showed no association between leprosy reactional states and BMI. Furthermore, BMI failed to correlate with the presence of reaction leprosy and deformities or multibacillary disease in the reported studies (p>0.05) [41,42]. Another study from Indonesia reported no significant association between poor nutrition and leprosy (p = 0.008, OR = 0.422) [43].…”
Section: Discussionmentioning
confidence: 77%